Understanding the Judge's Decisions which Are Best for Children to Realize Justice for all Post Diversion Failure - Adam Idris; Shamsul Anwar (Rechtsnormen: Journal of Law, 2026)
Background. The juvenile justice system prioritizes restorative justice through diversion to protect the rights and future development of children in conflict with the law. Nevertheless, diversion does not always achieve an agreement, creating legal challenges for judges in balancing the interests of child offenders, victims, and society while ensuring that judicial decisions remain consistent with the principle of justice for all. Purpose. This study aims to analyze judicial decisions rendered after the failure of diversion and to examine how judges uphold the best interests of the child within the broader framework of justice for all. Method. This research employs a normative legal research design focusing on judicial decisions as the primary object of analysis. The study relies exclusively on secondary data obtained through an extensive review of legal literature, including statutory regulations, judicial decisions, legal doctrines, and scholarly publications. Results. The findings reveal that the failure of diversion does not eliminate the obligation of judges to prioritize the best interests of the child. Judicial decisions are formulated by considering recommendations from the Correctional Center (BAPAS), legal advisors, and community perspectives, while also taking into account the interests of victims and the wider public. Conclusion. Judicial decisions following unsuccessful diversion continue to uphold the principle of the best interests of the child within the framework of justice for all. Such decisions demonstrate that juvenile sentencing should integrate rehabilitation, victim protection, and societal interests to achieve equitable and sustainable justice.